High-Temperature Tribology of AA5052/ZrB2 PAMCs - Kumar N.; Gautam G.; Gautam R.K.; Mohan A.; Mohan S. (My University, 2025)
AA5052/ZrB2 particulate aluminum matrix composites (PAMCs) have been produced by in situ reaction of K2ZrF6 and KBF4 compounds with molten alloy at about 860 °C. Dry sliding wear and friction of composites have been investigated for a particular sliding velocity and sliding distance at different loads from ambient temperature to 200 °C. It is revealed that for a particular load and temperature, wear rate and normalized wear rate decrease with increase in the volume percentage of ZrB2 particles whereas coefficient of friction (COF) shows a reverse trend. Wear rate and COF also increase with increase in temperature for a constant load and composition. Whereas with load for a particular temperature, wear rate and wear rate per unit vol. % ZrB2 increase while COF decreases. Worn surface and wear debris morphology examined under scanning electron microscopy (SEM) and profilometer to understand the wear mechanism revealed that wear mode transition takes place from mild-oxidative to severe-metallic at 100°C for unreinforced alloy, whereas a shifting is observed in transition temperature from 100 to 150°C for composite with 9 vol. % ZrB2 particles. Energy dispersive spectroscopy (EDS) analysis of worn surface confirms the oxidative wear mode. Profilometry results indicate that wear surface has higher surface roughness at higher values of load and temperatures. Prior to wear and friction studies, composites were also characterized by X-ray diffraction (XRD) and SEM for morphology and microstructural characteristics to correlate with wear results. The findings are very helpful to make the AA5052/ZrB2 composites suitable for the applications, where high-temperature wear is a limiting factor. Copyright © 2017 by ASME.